(untitled) (Educator Insights: Journal of Teaching Theory and Practice, 2025)
This article explores the representation of the central female character, Jennie Gerhardt, in Theodore Dreiser’s 1911 novel. The analysis focuses on how Dreiser constructs Jennie as a symbol of female virtue, suffering, and social constraint within the moral and economic structures of early 20th-century America. The study situates Jennie’s character within the broader context of American naturalism and examines the intersections of gender, class, morality, and determinism. Through a close reading of Dreiser’s narrative strategies and characterisation, the paper argues that Jennie Gerhardt embodies both the victimisation and quiet resistance of women in a patriarchal society.